Концептуальные разработки “новой экономической социологии” - Чернецкий, Ю. (Социология: теория, методы, маркетинг, 2004)
The history and contents of so called "New Economic Sociology" are analyzed in the article. Its two main concepts of the "embeddedness" and "the social construction (of the economy)" are explored. In this context the academic contribution of F.Dobbin,P.DiMaggio, N.Fligstein, M.Granovetter, A.Martinelli, D.Palmer, R.Swedberg,V.Zelizer and other contemporary sociologists is characterized. The conception of informal economy developed by M.Castells, E.Feige, L.Lomnitz, A.Portes, W.Powell And others is presented.